Effect of Coconut Fiber Reinforcement on Mechanical Properties of Corn Starch Bioplastics - Muhammad, Arbanah; Ramli Rashidi, Ahmad; Muhammad Hafiz Shah Buddin, Meor; ., . (International Journal of Engineering and Technology, 2018)
Plastic waste piling up in landfills is a serious threat to the environment. To minimize this type of waste, bioplastic made from various biodegradable sources is an option. In this work, bioplastic known as coconut fiber-corn starch bioplastic (CF-CSBP) is produced by incorporating a mixture of coconut fiber (CF), Lates calcarifer fish scale (FS) and glycerol, while the remaining is corn starch (CS). For a comparative study, a sample containing 0% CF known as corn starch bioplastic (CSBP) was also prepared. The effect of CF addition towards water absorption and mechanical characteristics; tensile strength, elongation and load to break were investigated. Results showed that CF-CSBP absorbed slightly more water (26.3%) after 24 hrs, but the addition of CF as a reinforcement improved the tensile strength and elongation to break the bioplastic. As for tensile, CF-CSBP was able to withstand higher force as compared to CSBP by 0.22 N/mm2. However, CF-CSBP only recorded 19.55% of elongation. This research proves the feasibility of using CF as a reinforcement material in the bioplastic and CF-CSBP is comparable to available bioplastics. Â Â